EFFICIENCY OF HORMONE THERAPY WITH LEIPRORELIN (LUCRIN DEPOT®) IN PATIENTS WITH PROSTATE CANCER - B. Ya. Alekseev (Onkourologiâ, 2011)
Prostate cancer (PC) is one of the most common cancers. Hormone therapy (HT) is the basic treatment for metastatic hormone-sensitive PC. HT with luteinizing-hormone-releasing hormone (LHRH) analogues is considered to be an effective method for hormone exposure as monotherapy and in combination with other drugs. Lucrin depot® is a potent and safe LHRH analogue whose efficacy has been proven by a number of clinical trials. This drug may be recommended as monotherapy or in combination with other hormonal agents in patients with PC if there are indications for androgen deprivation.